Perceived acceptability of an inhaled oxytocin for the prevention of postpartum haemorrhage in Ethiopia - Victoria L Oliver; Pete Lambert; Moti Tolera; Alula M Teklu; Abebaw Minaye; Michelle P McIntosh (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background New formulations and administration formats of oxytocin are required to overcome the current barriers to gold standard care for the prevention of postpartum haemorrhage (PPH) in low-resource settings. This study explored the potential acceptability of a heat-stable, inhaled oxytocin product in Ethiopia, a country with a high burden of PPH-related deaths. # Methods A qualitative research study design was employed in which focus group discussions and in-depth interviews were conducted with community members, healthcare providers and key informants. Research fields included: contextual acceptability (current attitudes toward PPH, oxytocin and inhaled or injectable medicines); product acceptability (attitudes towards an inhaled oxytocin product); and usage setting acceptability (acceptable settings for product use) # Results Acknowledgement of PPH as a significant maternal health issue and recognition of oxytocin as the gold standard of care for prevention will contribute to the contextual acceptability of an inhaled oxytocin product. An oxytocin inhaler was largely considered acceptable for use, with the heat stability viewed as a principal benefit. A non-injectable administration format that could be delivered by an individual with minimal training was also cited as an advantage. Concerns included the feasibility of attaining patient cooperation to inhale the dose correctly during the third stage of labour. While a high need for the product at out of facility deliveries was identified, births attended by a skilled healthcare provider will be the most acceptable setting for use from a health policy perspective. # Conclusions An inhaled oxytocin product is likely to be acceptable to relevant stakeholders in Ethiopia. This will facilitate adoption of the product and thereby enable improvements in maternal health outcomes.